The Childhood and Adolescent Taxon Scale – Self-Report: Validity Among Male and Female Youths from Forensic and School Contexts. Issue 1 (2nd January 2020) - Pechorro, Pedro; Seto, Michael C.; Alberto, Isabel; Ray, James V.; Simões, Mário R.
Abstract: This study provides the first examination of the Childhood and Adolescent Taxon Scale – Self-report (CATS-SR) proxy measure of the persistent antisocial behavior dimension of psychopathy, based on childhood and adolescent history, in a European context and with female youth. The CATS-SR is evaluated in a sample of 1, 134 male and female youth recruited from forensic or school settings in Portugal. The CATS-SR did not significantly differ for male and female youth seen in forensic settings, but was higher in male than female youth recruited from schools, and higher in youth seen in forensic than in school settings. The CATS-SR was positively and moderately correlated with self-report psychopathy construct measures that included items tapping interpersonal and affective facets of psychopathy such as callousness and impulsivity. It also correlated as expected with age of first criminal contact, crime seriousness, conduct disorder diagnosis, drug use, and having unprotected sex. The findings suggest that the CATS-SR has discriminant, convergent, and criterion-related validity, and could therefore be useful in assessments of the persistent antisocial dimension of psychopathy.